Hybrid threats in 21st century - theory and research of the term in Bosnia And Herzegovina - Kolobara, Robert (Array, 2020)
We live in the era of mass technology and global society bombarded by information and now more than ever we need to understand and assess the nature of communication and what it relays. Basis for the use of power and resources distribution has thus changed and it became quite obvious that the new methods of dissemination of messages to great distances, at considerably greater speed, will fundamentally change the nature of human interaction. In the contemporary world, interest and care for manipulation of public opinion, forming of attitudes and influence on behaviour reached unprecedented levels. Hybrid threats and wars became a first-class security issue of 21st century, and a sign and an indication of the security in the future. This work deals with theory and research of the term hybrid warfare and threats in Bosnia and Herzegovina through a sociological field survey of the population aiming to inductively establish the level of public knowledge on it.